THE ANALYSIS OF FACTORS IN THE FRAUD DIAMOND PERSPECTIVE AS PREDICTORS OF FRAUDULENT FINANCIAL REPORTING IN CONSTRUCTION COMPANIES LISTED ON IDX - Premananda, Ni Luh Putu Uttari; Kristina, Ni Made Rai; Wulandari, Putu Riska; Krisdayanthi, Astrid (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Fraudulent financial reporting fraud is a serious problem, especially in the construction sector, which is susceptible to manipulation. The study is intended to analyze the impact of four elements of fraud diamonds on the financial statements of fraud in Indonesia's construction sector (pressure, opportunities, rationalization, and capability). The data were collected from 21 construction companies listed on the Indonesian Stock Exchange (IDX) between 2020 and 2022, and totaled 63 observations. The analysis was conducted using multiple linear regression and the fraud score model (F-Score) as fraud detection tools. The results showed that all independent variables had positive and significant effects on financial fraud. Classical assumption tests ensure the validity of the model and the freedom from autocorrelation, multicollinearity and heteroscedasticity. This model explains 96.6% of changes in fraud in financial statements. The report recommended strengthening internal controls and developing mitigation strategies to reduce the risk of financial statements being forged.